2007
DOI: 10.1007/s11606-007-0239-8
|View full text |Cite
|
Sign up to set email alerts
|

“That’s Like an Act of Suicide” Patients’ Attitudes Toward Deactivation of Implantable Defibrillators

Abstract: Objective To understand potential patient barriers to discussions about implantable cardioverter defibrillator (ICD) deactivation in patients with advanced illness. Design Qualitative focus groups. Participants Fifteen community-dwelling, ambulatory patients with ICDs assigned to focus groups based on duration of time since implantation and whether they had ever received a shock from their device. Approach A physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
158
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(165 citation statements)
references
References 28 publications
5
158
0
2
Order By: Relevance
“…97 Qualitative studies have shown that patients may not fully understand how their ICDs work and develop complex psychological relationships with their devices that may contribute to a reluctance to deactivate the ICDs. 98 For end-stage heart failure patients, deactivation of ICDs when death is near is advisable to avoid repeated shocks in a dying patient. Particular care should be taken to make sure that such dialogue occurs early on, while the patient is still capable of participating in the discussion, and that it is clearly documented in the medical record.…”
Section: Icds and Cardiac Resynchronization Therapymentioning
confidence: 99%
“…97 Qualitative studies have shown that patients may not fully understand how their ICDs work and develop complex psychological relationships with their devices that may contribute to a reluctance to deactivate the ICDs. 98 For end-stage heart failure patients, deactivation of ICDs when death is near is advisable to avoid repeated shocks in a dying patient. Particular care should be taken to make sure that such dialogue occurs early on, while the patient is still capable of participating in the discussion, and that it is clearly documented in the medical record.…”
Section: Icds and Cardiac Resynchronization Therapymentioning
confidence: 99%
“…general practitioner (GP), cardiologist, heart failure nurse, palliative care clinician] they receive this information. 6,13,14 Little is known about how patients make sense of information about ICDs and what patients' information needs and preferences are with respect to implantation and deactivation. 5,6,15,16 By documenting current decision-making throughout the care pathway, and by exploring patients', family members' and clinicians' views of decision-making, we have addressed these knowledge gaps to help determine how to better support SDM about ICD implantation and deactivation.…”
Section: Methodsmentioning
confidence: 99%
“…11,14 Reasons for clinicians failing to initiate deactivation conversations were: a lack of knowledge about ICD function; poor quality doctor-patient relationships; the assumption that responsibility for discussing deactivation lies elsewhere; erroneous beliefs that patients are already aware that the device can be deactivated; and the belief that clinicians can accurately predict which patients will experience shock (and distress) towards the end of life. 11,24 This research suggests a level of unease around initiating deactivation discussions.…”
Section: Structure Of the Reportmentioning
confidence: 99%
“…However, we found that both the experience of fear and anticipation is elevated in patients after receiving the ICD. Fear of future shocks has been reported, regardless of whether patients had experienced a shock from the ICD [35] . The experience of fear has been reported to be increased when measured three and twelve months after implantation of an ICD [36] .…”
Section: The Intensity Of the Primary Emotionsmentioning
confidence: 99%